VALORILE EDUCAȚIEI ACTUALE ÎN EXTREMISMUL COTIDIAN (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Current education values in everyday extremism.In a global context marked by increasing ideological tensions, education plays a crucial role in shaping social attitudes and behaviors. Education systems can influence critical thinking, tolerance and inclusion, or conversely contribute tothe radicalization of young people through educational gaps and exposure to extremist narratives. The paper emphasizes the need for adapted educational interventions that promote democratic values and respect for diversity, thus contributing to combating extremism in contemporary society.